Antifungal potential of Melaleuca alternifolia (Maiden & Betche) Cheel against fungal pathogen Fusarium oxysporum f.sp. cubense Tropical Race 4 - Paramalingam, Pavitra (2022)
Fusarium wilt or Panama disease is recognised as one of the most destructive banana diseases in the world that is caused by Fusarium oxysporum f. sp. cubense, Tropical Race 4 (TR4). To date, only commercial fungicides are present to treat this disease. Plant extracts with antimicrobial properties attributable to their spectrum of secondary metabolites are actively being pursued. In this study, the inhibitory activities of five essential oils (Syzygium aromaticum, Cinnamomum verum, Alpinia conchigera, Eucalyptus globulus and Melaleuca alternifolia) and lima hydrosols (Eucalyptus globulus, Cinnamomum verum, Zingiber zerumbet, Ficus carica and Melaleuca alternifolia) on TR4 were investigated in vitro through agar well diffusion assay. Compared to fungicide, M. alternifolia oil and hydrosol were the most effective in suppressing the mycelial growth with percentage inhibition radial growth (PIRG) recorded at 69% and 45.32%, respectively. Broth macradilution assay revealed the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of M. alternifolia oil at 200 ppm and hydrosol at 50% v/v. Besides, spore germination assay revealed 0% inhibition of fungal spore germination at 300 ppm of oil and 3.3% inhibition at 100% hydrosol, respectively. From an in vivo study, M. alternifolia extracts significantly (p≤0.05) delayed Fusarium wilt symptom development in greenhouse-grown Berangan and Cavendish plantlets at all concentrations compared to control plantlets. The GC-MS analysis of M. alternifolia essential oil identified thirty-one bioactive compounds such as terpinen-4-ol, eucalyptol, à-terpineol and benzene, and 1-methyl-3-1-methylethyl. On the other hand, the LC-MS analysis of M. alternifolia hydrosol identified eighteen bioactive compounds including dihydro-jasmonic acid, methyl ester, L-galactono-1,4- lactone and diisopropyl sulfate. Hence, terpinen-4-ol from essential oil and Unknown compound 1 from hydrosol are suggested to be the best candidate that possesses fungicide properties against TR4. These findings indicate that M. alternifolia extracts could be used as natural alternatives to synthetic fungicides to control TR4.